Measurement of the branching fractions of the rare decays B-0 -> D-s((*)+)pi(-), B-0 -> D-s((*)+)rho(-), and B-0 -> Ds(*)-K(*)+ - Aubert, B; Bona, M; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Tico, J; Grauges, E; Lopez, L; Palano, A; et al. (2008)
We report the measurement of the branching fractions of the rare decays B0→Ds(*)+π-, B0→Ds(*)+ρ-, and B0→Ds(*)- K(*)+ in a sample of 381×106Υ(4S) decays into BB̄ pairs collected with the BA?B?AR? detector at the PEP-II asymmetric-energy e+e- storage ring. We present evidence for the decay B0→Ds-K*+ and the vector-vector decays B0→Ds*+ρ- and B0→Ds*-K*+, as well as the first measurement of the vector meson polarization in these decays. We also determine the ratios of the CKM-suppressed to CKM-favored amplitudes r(D(*)π) and r(D(*)ρ) in decays B0→D(*)±π and B0→D(*)±ρ, and comment on the prospects for measuring the CP observable sin (2β+γ). © 2008 The American Physical Society.